The Effect of Murottal Al-Quran on Anxiety Levels Toward IX Class Students in Facing Examination at The Junior High School of Muhammadiyah 1 Kalirejo Central Lampung - Dwi Oktarosada; Moh. Masrur; Eva Yunitasari; Hamid Mukhlis (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Anxiety is a psychological reaction in the form of bad feelings that can be experienced by anyone, including students who will undergo the National Examination. The level of anxiety that occurs depends on family support, environment and readiness to face something. Actions that can be taken to reduce anxiety include listening to murottal Al-Quran because listening to the Al-Quran can calm one's soul, so that it can reduce anxiety. The objective of the study was to determine the effect of murottal Al-Quran on the Anxiety Level of IX Class Students in Facing the National Examination. This study used a pre-experimental design with a one-group pretest-posttest design approach. The number of samples in this study were 94 students. The research instrument used in this study was the HARS (Hamilton Anxiety Rating Scale) questionnaire. Test analysis using Wilcoxon. The results showed that there was an effect of Murottal Al-Quran on the Anxiety Level of IX Class Students in Facing Exams at the Junior High School of Muhammadiyah 1 Kalirejo in Central Lampung with p-value 0.004 (p less than 0.05). It is expected that the results of this study can help the school as a reference method to reduce anxiety in students when facing exams by applying it continuously. Abstrak: Kecemasan merupakan reaksi psikisberupa perasaan tidak enak yang dapat dialami oleh siapa saja termasuk pada siswa/i yang akan menjalani Ujian Nasional. Tingkat kecemasan terjadi tergantung dari support keluarga, lingkungan serta kesiapan dalam menghadapi sesuatu. Tindakan yang dapat dilakukan untuk mengurangi kecemasan diantaranya mendengarkan murottal Al-Quran karena mendengarkan Al-Quran dapat menenangkan jiwa seseorang, sehingga dapat mengurangi kecemasan.Tujuan penelitian ini untuk mengetahui pengaruh murottal Al-Quran terhadap Tingkat Kecemasan Siswa/I Kelas IX Dalam Menghadapi Ujian Nasional.Penelitian ini menggunakan desain pre- eksperimen dengan pendekatan one group pretest-posttest design. Jumlah sampel dalam penelitian ini sebanyak 94 siswa. Instrument penelitian yang digunakan dalam penelitian ini adalah dengan menggunakan kuesioner HARS (Hamilton Anxiety Rating Scale). Uji analisis menggunakan Wilcoxon. Hasil penelitian menunjukkan bahwa ada pengaruh Murottal Al-Quran Terhadap Tingkat Kecemasan Siswa/I Kelas IX Dalam Menghadapi Ujian Di SMP Muhammadiyah 1 Kalirejo Lampung Tengah dengan nilai p-value 0,004 (p kurang dari 0,05). Diharapkan hasil penelitian ini dapat membantu pihak sekolah sebagai metode rujukan guna menurunkan cemas pada siswa/I ketika akan menghadapi ujian dengan cara mengaplikasikan secara terus menerus.